Morphology changes in bulk donor–acceptor poly(benzodithiophene‐benzotriazole) after post‐treatment. Issue 22 (2nd August 2016) - Zajaczkowski, Wojciech; Marszalek, Tomasz; Wong, Wallace W. H.; Pisula, Wojciech
ABSTRACT: The bulk order in donor–acceptor poly(benzodithiophene‐benzotriazole) was improved by two different post‐treatment procedures applied to the specimen. Two‐dimensional wide‐angle X‐ray scattering was used to investigate the structural changes after treatment. After post‐treatment the polymer turned into a highly crystalline morphology with well‐resolved and intensive π‐stacking reflections which were absent in the pristine sample. To understand the ordering mechanisms taking place during the two post‐treatment procedures, structural parameters like coherence length and paracrystallinity were extracted from the X‐ray data indicating the impact on crystallite size and cumulative lattice disorder. During temperature annealing the intralayer packing transforms from amorphous to highly ordered. On the other hand, solvent vapor annealing enhances in higher extent the interlayer organization due to interpenetration of solvent molecules between alkyl side chains. These results provide important insights for the morphology optimization of semicrystalline conjugated polymers. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 2327–2334. Abstract : The impact of two different post‐treatment procedures on the bulk morphology of donor–acceptor poly(benzodithiophene‐benzotriazole) is discussed. Based on wide‐angle X‐ray scattering, key structural parameters are extracted indicating the ordering mechanisms taking place during the two post‐treatments. These results provide important insights for the morphology optimization of semicrystalline conjugated polymers.